2020
DOI: 10.1002/ejic.202000204
|View full text |Cite
|
Sign up to set email alerts
|

Hexasubstituted Iodide Tungsten Cluster Complexes with Azide and Isothiocyanate Ligands

Abstract: The ever‐rising interest of researchers in octahedral halide cluster complexes is explained by their intrinsic superb luminescent properties. Nevertheless, to date chemistry of tungsten clusters, especially of iodide ones, has been poorly developed, and there is only a small number of known compounds. Two new compounds obtained in this work, (Bu4N)2[{W6I8}(NCS)6] (1) and (Bu4N)2[{W6I8}(N3)6] (2), expand the field of iodide tungsten clusters with inorganic ligands. The compounds are characterized by single crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…The cluster anion represent the 24-electron {W 6 I 8 } 4+ core with a slightly distorted {W 6 } octahedron. The average W-W and W-I distances (2.671(8) and 2.82(1) Å, respectively) are comparable with the corresponding values found in hexanuclear tungsten iodides with various terminal ligands [ 1 , 2 , 34 , 45 , 46 , 47 ]. Two W atoms in the trans -position are coordinated by CN − ligands, while four remaining W atoms in the equatorial plane are coordinated by a methylate anion ( Figure 5 b).…”
Section: Resultssupporting
confidence: 79%
“…The cluster anion represent the 24-electron {W 6 I 8 } 4+ core with a slightly distorted {W 6 } octahedron. The average W-W and W-I distances (2.671(8) and 2.82(1) Å, respectively) are comparable with the corresponding values found in hexanuclear tungsten iodides with various terminal ligands [ 1 , 2 , 34 , 45 , 46 , 47 ]. Two W atoms in the trans -position are coordinated by CN − ligands, while four remaining W atoms in the equatorial plane are coordinated by a methylate anion ( Figure 5 b).…”
Section: Resultssupporting
confidence: 79%
“…However, we have previously found that (TBA) 2 [W 6 I 8 (NO 3 ) 6 ] and (TBA) 2 [W 6 I 8 (N 3 ) 6 ] compounds are degraded by UV and blue light. 63,73 A similar situation was observed in the case of the cluster complex 4. When the crystals 4 were irradiated with light at a wavelength of 365 nm for 2 min, their color changed from yellow to brown as a result of the release of bromine (Figure S22).…”
Section: ■ Results and Discussionsupporting
confidence: 76%
“…Since there is no information on rate constants of 1 O 2 production by tungsten clusters or cluster-containing materials in water or, importantly, under white light, only indirect comparisons of effectiveness can be made. Nevertheless, k eff of 1 0.5 @pU (C 1 = 1.1 × 10 –5 M, concentration of 1 was calculated from ICP-AES data) is comparable to k eff of true solutions of pure tungsten clusters in CH 3 CN, such as (Bu 4 N) 2 [{W 6 I 8 }I 6 ] (C = 2 × 10 −5 M, λ ex = 365 nm, k eff = 0.049 min −1 ) or (Bu 4 N) 2 [{W 6 I 8 }(SCN) 6 ] (C = 2 × 10 –5 M, λ ex = 365 nm, 0.059 min –1 ) [ 17 ]. Note that, due to the low lifetime of singlet oxygen in H 2 O (about ~3.5 μs) [ 52 ] and less effective excitation of clusters with white light, we can conclude that 1 0.5 @pU is one of the most efficient cluster-based photosensitizers.…”
Section: Resultsmentioning
confidence: 99%
“…Such clusters have a stable cluster core {M 6 I 8 } 4+ that provides high photostability [ 13 ] and radiopacity due to the presence of heavy atoms [ 13 ]. Their generation of singlet oxygen under UV [ 14 , 15 , 16 , 17 ], white-light [ 18 , 19 , 20 ], and, most importantly, under X-rays [ 11 , 12 ] has also been proven, making them promising type II PSs for both conventional PDT and X-PDT. Despite the great prospects, to date there are only two studies demonstrating the X-ray-induced photodynamic effect of the clusters on living cells [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%